2021
DOI: 10.2138/am-2020-7350
|View full text |Cite
|
Sign up to set email alerts
|

Competitive adsorption geometries for the arsenate As(V) and phosphate P(V) oxyanions on magnetite surfaces: Experiments and theory

Abstract: This is the peer-reviewed, final accepted version for American Mineralogist, published by the Mineralogical Society of America. The published version is subject to change. Cite as Authors (Year) Title. American Mineralogist, in press.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 95 publications
1
11
0
Order By: Relevance
“…Additionally, according to recent studies, UiO-66 is an excellent phosphate adsorbent (up to a 415 mg/g phosphate uptake capacity, a higher capacity than most phosphate adsorbents) and the presence of phosphate can severely impact adsorption of arsenate by UiO-66. , For this study, the focus is narrowed on species present at neutral pH, i.e., H 2 AsO 4 – vs H 2 PO 4 – and HAsO 4 2– vs HPO 4 2– , and the double monodentate adsorption mode (Figure ). Our results show that adsorption of phosphates is thermodynamically competitive with arsenate adsorption, in agreement with previous computational studies on other materials as well as the observed competitive behavior of phosphates for adsorption sites on UiO-66. , Additionally, we found that phosphate coadsorption with arsenate is also thermodynamically viable and competitive, e.g., HAsO 4 2– /HPO 4 2– double monodentate binding mode is only 2.4 kcal/mol less favorable than both the HAsO 4 2– /HAsO 4 2– and HPO 4 2– /HPO 4 2– binding modes, thus potentially also contributing to decreased arsenate adsorption. Factors other than the binding strength between UiO-66 and the oxyanions may help further explain the detrimental effect of phosphates on arsenic adsorption.…”
Section: Resultssupporting
confidence: 92%
“…Additionally, according to recent studies, UiO-66 is an excellent phosphate adsorbent (up to a 415 mg/g phosphate uptake capacity, a higher capacity than most phosphate adsorbents) and the presence of phosphate can severely impact adsorption of arsenate by UiO-66. , For this study, the focus is narrowed on species present at neutral pH, i.e., H 2 AsO 4 – vs H 2 PO 4 – and HAsO 4 2– vs HPO 4 2– , and the double monodentate adsorption mode (Figure ). Our results show that adsorption of phosphates is thermodynamically competitive with arsenate adsorption, in agreement with previous computational studies on other materials as well as the observed competitive behavior of phosphates for adsorption sites on UiO-66. , Additionally, we found that phosphate coadsorption with arsenate is also thermodynamically viable and competitive, e.g., HAsO 4 2– /HPO 4 2– double monodentate binding mode is only 2.4 kcal/mol less favorable than both the HAsO 4 2– /HAsO 4 2– and HPO 4 2– /HPO 4 2– binding modes, thus potentially also contributing to decreased arsenate adsorption. Factors other than the binding strength between UiO-66 and the oxyanions may help further explain the detrimental effect of phosphates on arsenic adsorption.…”
Section: Resultssupporting
confidence: 92%
“…We note that the model underestimated the suppression of arsenate adsorption to gibbsite when phosphate was present. Given the EXAFS analysis showed more evidence for outer-sphere surface complexes of arsenate on gibbsite (e.g., lower CN Al ) and the recent observation of arsenate outer-sphere complex on magnetite surfaces by attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectrum, we speculate that the outer-sphere complexation, which is not specifically accounted for in the present models, may provide additional capacity for arsenate uptake when phosphate is competing.…”
Section: Resultsmentioning
confidence: 67%
“…The D2 semiempirical method of Grimme was included in our calculations to correct the long-range dispersion interactions, 75 which is particularly important for an appropriate description of materials and interface properties. 59,68,[76][77][78][79][80][81][82][83][84][85] periodic plane-wave basis set with an upper kinetic energy threshold fixed at 400 eV was employed to expand the Kohn-Sham valence states. The electronic ground state was determined using a preconditioned conjugate gradients minimisation algorithm, which optimises completely and self-consistently the total (free) energy, which is the variational quantity within this methodology.…”
Section: Calculation Detailsmentioning
confidence: 99%